ANALISIS TEKSTUAL BRAND TELUK LOVE MENJADI DESTINASI WISATA POPULER DI KABUPATEN JEMBER - Ari Susanti (Universitas Muhammadiyah Jember, 2018)
Love Bay, which is located in Payangan Hamlet, Sumberrejo Village, Ambulu District, Jember Regency, is one of the most popular tourist destinations today. The word